2019
DOI: 10.1097/ico.0000000000001945
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up of Intrastromal Corneal Ring Segment Implantation in Pediatric Keratoconus

Abstract: Purpose: To evaluate efficacy, safety, and stability of Ferrara-type intrastromal corneal ring segment (ICRS) implantation for visual rehabilitation in pediatric patients with keratoconus. Methods: This study included patients with keratoconus aged 18 years or younger who had received Ferrara-type ICRS implantation. The uncorrected and corrected distance visual acuities, residual refractive errors, and root mean square for coma-like aberration were recorded preoperatively and at 6 months, 1, 3, and 5 years pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…Recently, Sedaghat and colleagues [27] confirmed in adult patients implanted with the same type of ICRS (KeraRing) that a greater difference between the preoperative uncorrected and corrected distance visual acuity and more coincidence of the most elevated points in the two corneal surfaces on the elevation maps increased the rate of successful outcome. Despite the non-statistically significant change in refraction, significant modifications were found in the current series in keratometric readings, the magnitude of corneal astigmatism, and logMAR CDVA, as in previous series using the same and other type of ICRS in adults and children [12][13][14]. Specifically, significant central corneal flattening, reduction of magnitude of astigmatism and improvement of CDVA were observed, with 52.8% of eyes showing a reduction in the magnitude of anterior corneal astigmatism of 1 D or more.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Recently, Sedaghat and colleagues [27] confirmed in adult patients implanted with the same type of ICRS (KeraRing) that a greater difference between the preoperative uncorrected and corrected distance visual acuity and more coincidence of the most elevated points in the two corneal surfaces on the elevation maps increased the rate of successful outcome. Despite the non-statistically significant change in refraction, significant modifications were found in the current series in keratometric readings, the magnitude of corneal astigmatism, and logMAR CDVA, as in previous series using the same and other type of ICRS in adults and children [12][13][14]. Specifically, significant central corneal flattening, reduction of magnitude of astigmatism and improvement of CDVA were observed, with 52.8% of eyes showing a reduction in the magnitude of anterior corneal astigmatism of 1 D or more.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have confirmed the validity of CXL [11] and contact lenses fitting of special designs, such as scleral lenses [17], for the management of keratoconus, even in children [18][19][20][21]. Likewise, some studies have shown the potential of the use of ICRS in keratoconus in children, allowing a regularization of the corneal surface, an improvement of visual quality and even an improvement in contact lens tolerance [13,14,22,23]. In most of the cases, this implantation was combined with CXL [22,23].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations